Аналіз факторного простору показників ефективності логістичної діяльності за глобальними рейтинговими оцінками країн світу - Сергієнко, Олена Андріанівна; Гапоненко, Ольга Євгенівна (My University, 2020)
У статті проведено кластерний та канонічний аналіз за індексом ефективності логістики (LPI), який використовується для вимірювання ефективності міжнародних ланцюгів постачання. Дослідження охоплює 160 країн світу. Країни оцінюються за п’ятибальною системою за декількома окремими характеристиками логістичної сфери: ефективність митної обробки вантажу, можливості організації міжнародних вантажовідправлень, ефективність місцевої логістичної інфраструктури, контроль і відстеження міжнародних вантажовідправлень, витрати на логістику всередині країни, своєчасність доставки вантажів у пункти призначення. За результатами кластерного аналізу встановлено, що Україна належить до другої групи країн із середнім рівнем логістичного розвитку. Канонічний аналіз показав, що між множинами характеристик логістичної сфери та їх результативними показниками існує суттєва залежність, і найбільший внесок у залежність роблять змінні "митниця", "інфраструктура" та "загальний бал оцінки логістичної діяльності".

The article deals with cluster and canonical analyzes on the Logistics Performance Index (LPI), which is used to measure the effectiveness of international supply chains. The study covers 160 countries. Countries are evaluated on a five-point system based on several separate characteristics of the logistics sector: the efficiency of customs cargo handling, the possibility of organizing international cargo shipments, the efficiency of local logistics infrastructure, control and tracking of international cargo shipments, the cost of logistics within the country, timely delivery of goods. Ukraine ranks 66th among the countries in the logistic efficiency index and is the leader among the CIS countries in 2018. As a result of the cluster analysis of the characteristics of the logistics sector, it is established that countries can be divided into three groups according to the level of development of each of the components: "most logistically developed" "moderately developed" and "weakest". Ukraine belongs to the second cluster. According to this analysis, we can conclude that Ukraine has a more or less efficient logistics system with a number of disadvantages and has a great prospect of entering the cluster of "most logistically developed countries". The main focus should be on the most influential indicators: quality of logistics and competence, work of customs, tracking of freight. The interconnection and interdependence of logistic sphere characteristics was investigated using canonical analysis. It is established that there are significant dependencies between sets of characteristics of logistic sphere and productive indicators, and customs, infrastructure and overall score of logistic activity make the greatest contribution to dependence. The conducted study of the main factors and tendencies of market development made it possible to distinguish the main external risks and threats, among which: slowdown of dynamics of macroeconomic indicators, high risk of devaluation of the national currency, falling demand in foreign markets for export products; high cost of credit and investment resources; increased competition from foreign companies; further increase in the cost of production.
Analysis of the factor space of performance logistic activity indicators by global rating evaluations of the world
Keywords: економічна діяльність; логістика; канонічний аналіз; кластерний аналіз; промислові підприємства; ринкові відносини; factor space; logistic activity; logistics performance index; canonical analysis; cluster analysis